1994
DOI: 10.1021/jm00033a006
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 3-Substituted Benzazepinone Growth Hormone Secretagogue (L-692,429)

Abstract: The 3-substituted benzazepinone, L-692,429 (compound 1), is the prototype compound of a novel class of compounds that stimulate release of growth hormone (GH). The molecule evolved from efforts to identify a non-peptide mimic of the growth hormone-releasing hexapeptide, GHRP-6. Compound 1 is prepared by sequential attachment of dimethyl-beta-alanine and 2'-biphenylyltetrazole side chains to a chiral 3-aminobenzolactam nucleus. Comparison of the biological activity of 1 with the corresponding six- and eight-mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…Using those parameters, the screening of Merck chemical sample collection spotted a racemic benzolactam 2 as a potential lead for GH release stimulation (EC 50 = 3 µM). Further pharmacomodulation of 2 converged in the synthesis of L‐692,429 3 , highly active in vitro (EC 50 = 30 nM) and in vivo 131–133. It succeeded preclinical safety and toxicology studies and was active in human134, 135.…”
Section: Ghrelin Analogues and Their Biological Activitymentioning
confidence: 95%
“…Using those parameters, the screening of Merck chemical sample collection spotted a racemic benzolactam 2 as a potential lead for GH release stimulation (EC 50 = 3 µM). Further pharmacomodulation of 2 converged in the synthesis of L‐692,429 3 , highly active in vitro (EC 50 = 30 nM) and in vivo 131–133. It succeeded preclinical safety and toxicology studies and was active in human134, 135.…”
Section: Ghrelin Analogues and Their Biological Activitymentioning
confidence: 95%
“…4,5 Significant progress has been made toward identifying small molecules that mimic the mechanism of action and in vivo properties of GHRP-6. Examples are the benzolactam L-692,429 6,7 (2, Figure 1) and the spiropiperidine-based MK-0677 8 (3, Figure 1). Experiments in rat primary pituitary cells indicated that L-692,429 and MK-0677 are mechanistically indistinguishable from the hexapeptide GHRP-6 and, hence, are peptidomimetic agonists.…”
Section: Introductionmentioning
confidence: 99%
“…First, screenings of small-molecule chemical libraries resulted in nonpeptide in vitro active GH secretagogues. The benzolactam compound L-158,077 [155] directed design towards biphenyltetrazoles such as MK-0751 (L-692,429). MK-0751 releases GH in vitro [155] and in vivo in animals [156] and in humans [157][158][159].…”
mentioning
confidence: 99%
“…The benzolactam compound L-158,077 [155] directed design towards biphenyltetrazoles such as MK-0751 (L-692,429). MK-0751 releases GH in vitro [155] and in vivo in animals [156] and in humans [157][158][159]. Another initial hit from a chemical library, L-368,112, led the design toward the agonist with partial peptide properties ibutamoren (L-163,191, mesylate salt form MK-0677) [160], which has been extensively studied in animals and humans.…”
mentioning
confidence: 99%